ANALISIS PROSEDUR PENGAJUAN UPAYA HUKUM BANDING WAJIB PAJAK KE PENGADILAN PAJAK DI FIRMA HLP CONSULTANT BANJARMASIN - Afritriani, Mega; Saipudin; Mellani Yuliastina (Universitas Lambung Mangkurat, 2022)
This research analyzes the Procedure for Submitting Taxpayer Appeals to the Tax Court at the HLP Consultant Banjarmasin Firm. So that taxpayers know that we can file an appeal if the taxpayer is overpaid in paying taxes, in order to understand the systematics of resolving tax disputes in the judicial mechanism in Indonesia, and the purpose of this research is to review and examine the causality of the Tax Court and the Supreme Court in Judicial Power.